Comparative analysis of single- and multi-criteria container transport modes in Peninsular Malaysia - Gohari, A. (Taylor and Francis Ltd., 2020)
This study investigates the transport of containers via intermodal transport network of Peninsular Malaysia by comparatively analysing the use of trucks, trains and ships with respect to time, CO2 emission and cost. The study is aimed at proposing the best route/mode of container transport in Peninsular Malaysia. ArcMap and MATLAB were employed to identify the single-objective route/modal choices. The multi-criteria route/modal choices were achieved by integrating the Simple Multi-Attribute Rating Technique (SMART) and sensitivity analysis. The single-objective results indicated that the use of trucks on road was the fastest mode of container transport. However, the combination of ship and train was the most environmental-friendly for Case 1, while transport by ship generated the least CO2 emission for Case 2. Train was found to be the cheapest mode of container transport, followed by ship and truck. It can be inferred from the multi-criteria analysis that container transport via rail is the ideal and least-cost route and mode of transport. Â© 2020, Â© 2020 Informa UK Limited, trading as Taylor & Francis Group.